2015
DOI: 10.1021/acs.jnatprod.5b00781
|View full text |Cite
|
Sign up to set email alerts
|

Bioactiveent-Pimarane andent-Abietane Diterpenoids from the Whole Plants ofChloranthus henryi

Abstract: Two new ent-pimarane (1 and 2), eight new ent-abietane (3-10) diterpenoids, and eight known analogues (11-18) were isolated from the whole plants of Chloranthus henryi. The absolute configuration of 1 was determined on the basis of single-crystal X-ray diffraction data. Compound 8 represents a class of rare naturally occurring C-14 norabietanes, and compounds 9 and 10 feature rare 13,14-seco-abietane skeletons. Compounds 5, 12, 13, and 15 inhibited the yeast-to-hyphae transition of Candida albicans with IC50 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
1
8
0
1
Order By: Relevance
“…341.2451) in positive HR‐ESI‐MS. The molecular formula and NMR data of 3 were similar to those of 13‐ O ‐methylsessilifol D (C 21 H 34 O 3 ), [23] except for the absence of a hydroxy group. Furthermore, the very minor difference of the 13 C‐NMR data for both ring B and ring C between the two compounds indicated that 3 was a 3‐dehydroxy derivative of 13‐ O‐ methylsessilifol D. This deduction was confirmed by the key HMBCs from methoxy protons ( δ (H) 3.22 (s, 3H)) to C‐13 ( δ (C) 75.6), from H‐14 ( δ (H) 6.80, br.…”
Section: Resultsmentioning
confidence: 73%
“…341.2451) in positive HR‐ESI‐MS. The molecular formula and NMR data of 3 were similar to those of 13‐ O ‐methylsessilifol D (C 21 H 34 O 3 ), [23] except for the absence of a hydroxy group. Furthermore, the very minor difference of the 13 C‐NMR data for both ring B and ring C between the two compounds indicated that 3 was a 3‐dehydroxy derivative of 13‐ O‐ methylsessilifol D. This deduction was confirmed by the key HMBCs from methoxy protons ( δ (H) 3.22 (s, 3H)) to C‐13 ( δ (C) 75.6), from H‐14 ( δ (H) 6.80, br.…”
Section: Resultsmentioning
confidence: 73%
“…The pimarane derivatives are a class of tricyclic diterpenoids with a fused 6/6/6 ring system, which were mainly found in plants, such as Ceriops decandra , Sigesbeckia orientalis , Sigesbeckia pubescens , Ambrosia arborescens , and Boesenbergia pandurate , while rarely discovered from fungi of Aspergillus wentii , Eutypella sp., and Eutypella scoparia . Pimarane diterpenoids have attracted much attentions of chemists and pharmacologists because many of them featured a broad spectrum of biological activities, for example cytotoxic, antibacterial, anti‐inflammatory, TRAIL‐resistance‐overcoming, and Candida albicans morphogenesis inhibitory activities . The fungus Botryotinia fuckeliana MCCC 3A00494 was obtained from the deep‐sea water by sampling from the western Pacific Ocean at a depth of 5572 m, from which we isolated 71 new and eight known aphidicolin diterpenoids .…”
Section: Introductionmentioning
confidence: 99%
“…For example, chlorabietins B and C, two 13,14- seco -abietanes, showed antineuroinflammatory effects by inhibiting the nitric oxide (NO) production in lipopolysaccharide (LPS)-activated murine BV-2 microglial cells . To date, more than 80 naturally occurring seco -abietane diterpenoids have been reported. Particularly, hyptisolode A is a bis- seco -abietane, and its C-7/C-8 bond (B-ring) and the C-11/C-12 bond (C-ring) both have been cleaved by oxidation …”
mentioning
confidence: 99%